2007
DOI: 10.2340/16501977-0104
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent low back pain: Relapse from a patients perspective

Abstract: Objective: To explore and describe how patients with recurrent low back pain perceive and respond to the recurrence of pain. Design: A semi-structured interview study. Subjects: Seventeen patients (10 women and 7 men) with recurrent low back pain. Methods: Semi-structured interviews were analysed using the phenomenographic method. Results: Patients' perceptions of relapse of low back pain could be divided into 4 different categories: (i) an unsolved mystery, a source of uncertainty and self-accusation; (ii) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Further research on the predictors and moderators of illness uncertainty may provide us with an answer to help individ uals cope with acute and chronic pain and potentially improve their physical and psychological health. Benjaminsson et al [46] 2007 Low back pain; n = 17 Perceptions of back pain relapse were categorized as: a source of uncertainty and self-accusation; an obvious part of life that has to be ignored; a reminder to keep within physical and psychological limits; and an indication to change behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research on the predictors and moderators of illness uncertainty may provide us with an answer to help individ uals cope with acute and chronic pain and potentially improve their physical and psychological health. Benjaminsson et al [46] 2007 Low back pain; n = 17 Perceptions of back pain relapse were categorized as: a source of uncertainty and self-accusation; an obvious part of life that has to be ignored; a reminder to keep within physical and psychological limits; and an indication to change behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies A number of qualitative studies also have examined the concept of illness uncertainty in the context of chronic pain conditions, including low back pain, RA, and unexplained chest pain [46][47][48][49][50][51] (Table 1). These studies found that illness uncertainty was a salient experience for all of these pain conditions.…”
Section: Other Chronic Illnessesmentioning
confidence: 99%
“…l included people younger than 18 years [70][71][72][73][74][75] l case study or auto-ethnography [76][77][78][79][80][81] l chronicity of pain was not explicit in the sample description l reported conditions other than MSK pain l did not explicitly state that it was specifically about MSK pain l included perceptions of others such as family members, carers, clinicians l included those with pain of < 3 months in duration l did not meet the specific scope, for example explored perceptions of fatigue or exercise [266][267][268][269][270][271][272][273][274][275][276][277][278][279][280] l explored the experience of chronic disease rather than chronic pain. [281][282][283][284][285][286][287][288][289][290][291][292][293][294][295] Ninety-three studies 66,296-387 met the study scope and were appraised (see Figure 9).…”
Section: Search and Screeningmentioning
confidence: 99%
“…Women led a sedentary lifestyle and limited their social activities, relied heavily on medication, and shaped their illness behaviours in relation to the expectations of others. Benjaminsson et al (2007) explored and described how patients with recurrent LBP perceive and respond to the recurrence of pain. Some patients in this study undertook a passive approach, where movement was avoided, and where they constantly looked for medical solutions to diminish their pain.…”
Section: Illness Identities and Coping With Chronic Illnessmentioning
confidence: 99%